John Calvin : a pilgrim's life - Selderhuis, H. J., 1961- (Downers Grove, Ill. : IVP Academic, 2009)
Selderhuis draws on Calvin's own publications and commentary on the biblical figures with whom he strongly identified to describe his theology in the context of his personal development. Throughout we see a person who found himself alone at many of the decisive moments of his life--a fact that echoed through Calvin's subsequent sermons and commentaries. Selderhuis's unique and compelling look at John Calvin, with all of his merits and foibles, ultimately discloses a man who could not find himself at home in the world in which he lived. --from publisher description
Orphan (1509-1533) -- Pilgrim (1533-1536) -- Stranger (1536-1538) -- Refugee (1538-1541) -- Preacher (1541-1546) -- Victim (1546-1549) -- Widower (1549-1551) -- Patient (1551-1554) -- Sailor (1555-1559) -- Soldier (1559-1564).
Includes bibliographical references (p. [260]-285) and index.
Keywords: Calvin, Jean, -- 1509-1564.; Reformation -- Biography